2014
DOI: 10.17221/76/2013-jfs
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of ground-based logging equipment on forest soil

Abstract: Soil properties can be affected by heavy equipment used for skidding but these impacts vary greatly with site conditions and operational practices. We assessed the effects of ground-based skidding on site disturbance and soil physical properties. We also tested the effects of skid trail slope and traffic frequency on soil compaction, total porosity, and moisture content. On average, about 30% of all harvested area was disturbed to varying levels. Intact forest floor (undisturbed) and light slash were the domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 21 publications
1
32
1
3
Order By: Relevance
“…The extent of soil disturbance was reported 30% by Solgi & Najafi (2014). The results indicated that the soil bulk density in the ruts during winching of logs and in the skid trails are significantly higher than the soil bulk density in the controlled areas.…”
Section: Soil Disturbancementioning
confidence: 95%
See 1 more Smart Citation
“…The extent of soil disturbance was reported 30% by Solgi & Najafi (2014). The results indicated that the soil bulk density in the ruts during winching of logs and in the skid trails are significantly higher than the soil bulk density in the controlled areas.…”
Section: Soil Disturbancementioning
confidence: 95%
“…In addition, 504 points were recorded for assessing visual soil disturbance (B.C. Ministry of Forests, 2001;Solgi & Najafi, 2014). Length, width and deep of ruts (larger than 200, 30 and 5 cm, respectively) that intersected by transects were measured.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…It is important to follow the growth and development of planted and self‐seeded seedlings as well as the ground and field vegetation at these sites to assess the overall long‐term impacts of off‐road traffic. Skid trails or wheel tracks normally cover about 12 to 30% of the clearcuts (Brais, 2001; Eliasson, 2005; Mohtashami et al, 2017; Solgi and Najafi, 2014), and reduced soil aeration in some parts may be of less importance for the future stand, especially if they are subjected to soil scarification. However, more investigations are needed on these matters.…”
Section: Discussionmentioning
confidence: 99%
“…Lalu lintas alat sarad juga dapat menyebabkan pemadatan tanah pada 52% area plot (Missanjo & Thole, 2014). Pemadatan tanah terjadi pada jalur (track) alat sarad, dimana kepadatan tanah, porositas tanah dan kadar air sangat dipengaruhi oleh frekuensi lalu lintas alat sarad dan kemiringan jalan sarad (Solgi & Najafi, 2014). Permukaan tanah 0-10 cm pada area penyaradan terjadi pemadatan tanah.…”
Section: Pendahuluanunclassified